2007
DOI: 10.1063/1.2824395
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of random laser and coherent backscattering of light from ZnO amplifying random medium

Abstract: We investigated the dynamics of coherent backscattering cone and random laser in a disordered gain medium of ZnO powder. Theoretical fit to the coherent backscattering cone yields a transport mean free path l approximately equal to the probe wavelength , indicating that the scattering process is in the strong scattering regime. Supernarrow emissions from the laser are accompanied by enhancement and sharpening of the coherent backscattering cone. This enhanced and sharpened backscattering cone returns to a norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A technical challenge is the high speed required for temporal modulation. Prior experimental studies with pulsed excitations have revealed fast dynamic response of random lasers [8][9][10][11][12][13][14][15][16][17][18][19][20], and the pump modulation needs to be on a comparable time scale.…”
Section: Introductionmentioning
confidence: 99%
“…A technical challenge is the high speed required for temporal modulation. Prior experimental studies with pulsed excitations have revealed fast dynamic response of random lasers [8][9][10][11][12][13][14][15][16][17][18][19][20], and the pump modulation needs to be on a comparable time scale.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of new nanomaterials and the detail understanding of the photophysics of the nanowires are of major importance for both fundamental research and future nanotechnology applications. In the past decade, most efforts on fabrication and study of the physical and optical properties of nanowires or nanostructures were based on inorganic materials. , Considerable success was noted in ZnO- and GaN-based nanomaterials with demonstration of laser, light-emitting diode and photodetector from single nanowires …”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] CBM may find applications in real time correction of dynamic phase distortions (aberrations) in passive and active optical components such as correcting phase distortions in a multi-pass amplifying system. The CBM enhancement profile can be used to conveniently quantify local optical properties of a random medium in biomedical applications and remote sensing in general.…”
Section: 26mentioning
confidence: 99%